Ecoeficiência e sustentabilidade nutricional em povoamentos de eucaliptos no bioma Pampa - Guimarães, Claudiney do Couto (2016)
The expansion of plantations with eucalyptus in Rio Grande do Sul state have been consolidating and occupying areas that anteriorly had no silvicultural tradition in commercial scale. The state occupies the sixth position in planted areas with eucalyptus and pinus in the country and although a significant part of the cultivated area is established in the Pampa Biome, few studies have been conducted to understand the behavior of eucalyptus in this ecosystem. Therefore this study aimed to determine the efficiency of Eucalyptus dunnii, Eucalyptus grandis, Eucalyptus benthamii, Eucalyptus saligna and hybrid of Eucalyptus urophylla x Eucalyptus grandis (E. urograndis), at seven years of age, and provide elements for nutrition and sustainable forestry management. To this it was estimated stock of total and available nutrients in the soil up to 100 cm deep; it was determined the growth; biomass and nutrients were quantified above and below ground for different species; were evaluated the silvicultural and ecological implications of the removal of nutrients due to the different biomass harvesting scenarios; and alternatives have been proposed for forestry management and fertilization. The soil in the study area is classified as Ultisol. Samples were collected for physical and chemical soil characterization. They were inventoried five sample units of 10 ha, one for each species, to determine the growth variables. After the measurements distribution was performed by diameter classes, which were determined three classes, the first class of 10 to 16 cm, the second 16.1 to 22 cm and the third class of 22.1 to 28 cm. To determine the tree biomass in Mg ha-1, three trees were selected by diameter class being a tree at the lower limit, a tree in the central limit and a tree at the upper limit of each class, totaling nine trees by species. The trees were cut into compartments, sampling for determination of individual tree biomass and nutrient content. The soils of the experimental areas had textural class 4 (clay content < 20%), with significant differences between the chemical attributes in relation to native field, highlighting the increased levels of P, K and S for the majority of species. The highest annual mean increment and total volume were observed in E. saligna (61.10 m³ ha-1 to 427.55 m³ ha-1) followed by the E. grandis (54.84 m³ ha-1 m³ and 383.88 ha-1 E. urograndis (54.25 m³ ha-1 and 379.78 m³ ha-1), E. benthamii (49.87 m³ ha-1 and 349.11 m³ ha-1) and E. dunnii (45, 97 m³ ha-1 and 321.80 m³ ha-1). The highest biomass production was observed in E. saligna, with 289.94 Mg ha-1; followed by E. urograndis with 231.66 Mg ha-1; E. grandis, with 228.51 Mg ha-1; E. benthamii with 225.35 Mg ha-1 and E. dunnii with 205.62 Mg ha-1, with allocation of biomass in stem wood of 74% E. urograndis and E. grandis, 70% for E. saligna, 69% for E. benthamii and 67% for E. dunnii. The magnitude of biomass allocation presented the same tendency among species – stem wood > root > branch > bark > leaf. The highest concentration of N, P, K, S, B, Cu and Mn was observed in leave; stem wood showed the highest concentration of Ca and Mg, and the root of the highest concentration of Fe and Zn. The greatest amount of nutrients was observed in the stem wood, except for Ca and Mg, where larger quantities are allocated in the bark of the wood and the Fe that is allocated at the root. In the litter there was the same distribution behavior for the nutrients (concentrations and quantities) – Ca > N > Mg > K > S > P – Mn > Fe > B > Zn > Cu. The highest values for the nutrients utilization efficiency were observed in E. grandis, E. saligna and E. dunnii for P; E. urograndis and E. benthamii for Mg; E. saligna for S; E. grandis also presented the better efficiency in N, K and Ca. The harvest only the stem wood provided a maintenance of soil nutrients by other components of the biomass, greater than 50%, especially Ca and Mg with a return of 82% and 72% respectively. The lowest nutrient removal rate according to the intensity of biomass harvesting was verified in E. grandis. For the production number of rotations, the P indicated a nutritional sustainability condition under all harvesting scenarios, the N in the harvesting of the stem wood over bark and stem wood, Ca and Mg in the harvesting of the stem wood, for all species; and the K was the element that presented the greatest productivity risk limiting. The lower cost of nutritional replacement, among biomass harvesting scenarios, was found in E. grandis followed by E. urograndis, E. dunnii, E. saligna and E. benthamii.